2020
DOI: 10.1002/chem.201904762
|View full text |Cite
|
Sign up to set email alerts
|

Concurring Chalcogen‐ and Halogen‐Bonding Interactions in Supramolecular Polymers for Crystal Engineering Applications

Abstract: The engineering of crystalline molecular solids through the simultaneous combination of distinctive non‐covalent interactions is an important field of research, as it could allow chemist to prepare materials depicting multi‐responsive properties. It is in this context that, pushed by a will to expand the chemical space of chalcogen‐bonding interactions, a concept is put forward for which chalcogen‐ and halogen‐bonding interactions can be used simultaneously to engineer multicomponent co‐crystals. Through the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 132 publications
1
59
0
6
Order By: Relevance
“…Analysis of Chalcogen Bonds using SAPT Calculations Our studies were focused on investigations of the nature of strong chalcogen bonds that exist primarily between tellurium-containing nitrogen heterocycles and different Lewis bases. [12,15,17,18,21,[30][31][32][33] Thelatter are for instance oxygen or nitrogen atoms of heterocycles or amides.Inthis study,we chose tellurium-containing aromatics as model compounds and calculated the dimers and their complexes with acetamide,t rimethylamine,t rimethylphosphine,t etrachloromethane and pyridine ( Figure 1). Forc omparison purposes the corresponding sulfur-a nd selenium-containing complexes were also investigated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Analysis of Chalcogen Bonds using SAPT Calculations Our studies were focused on investigations of the nature of strong chalcogen bonds that exist primarily between tellurium-containing nitrogen heterocycles and different Lewis bases. [12,15,17,18,21,[30][31][32][33] Thelatter are for instance oxygen or nitrogen atoms of heterocycles or amides.Inthis study,we chose tellurium-containing aromatics as model compounds and calculated the dimers and their complexes with acetamide,t rimethylamine,t rimethylphosphine,t etrachloromethane and pyridine ( Figure 1). Forc omparison purposes the corresponding sulfur-a nd selenium-containing complexes were also investigated.…”
Section: Resultsmentioning
confidence: 99%
“…[1] In the beginning the basic concept of chalcogen bonding was focused, [2][3][4][5][6][7][8] whereas in recent times,t he use of strong chalcogen bonds has become an object of interest. [9][10][11] It could be shown that this bond type can also be used for crystal engineering, [12][13][14] molecular recognition in solution [15][16][17][18][19][20][21] and catalysis. [11,20,[22][23][24][25][26][27][28] Very strong and promising chalcogen bonds are found in electron-poor tellurium compounds such as isotellurazole oxides [21,29] or telluradiazole.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Der Fokus unserer Studien lag auf der Untersuchung der Natur starker Chalkogenbindungen, die vornehmlich zwischen tellurhaltigen Stickstoff‐Heterocyclen und verschiedenen Lewis‐Basen existieren [12, 15, 17, 18, 21, 30–33] . Letztere sind beispielsweise Sauerstoff‐ oder Stickstoffatome von Heterocyclen oder Amiden.…”
Section: Ergebnisse Und Diskussionunclassified
“…Diese tellurhaltigen Systeme bilden in Lösung stark assoziierende Dimere und Oligomere [21] und können deshalb als molekulare Erkennungseinheiten in der supramolekularen Chemie eingesetzt werden [18] . Neben Isotellurazoloxiden und Tellurdiazolen werden neuerdings auch Tellurazole als vielversprechende Bausteine zum Aufbau starker Chalkogenbindungen verwendet [12, 32] . Es konnte gezeigt werden, dass die intermolekularen Wechselwirkungen zwischen dem Telluratom des Tellurazols und dem Sauerstoffatom einer Amidgruppe zur Bildung supramolekularer Drähte und organischer Gerüstverbindungen in fester Phase führen [33] …”
Section: Introductionunclassified